ACHIEVEMENT OF ANTENATAL CARE VISIT K4 PREGNANT WOMEN WITH THE SUPPORT OF HEALTH WORKERS: A LITERATURE REVIEW - Lili Jenni Suebu; Andi Nilawati Usman; Mardiana Ahmad (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Antenatal Care services are still a point of concern in efforts to improve the health and safety of mothers and babies. This service is not only of quantity but of the quality provided to pregnant women. The scope of K4 antenatal service visits in Papua Province is 29,149 pregnant women (37%); this is still far from the national target of 90%. Objectives: This study aimed to find out the influence of health worker support in achieving antenatal visits K4 in pregnant women using literature studies. Design: The method used in writing this article is a systematic review. Data Sources: Search for articles using Google Scholar were databased by entering the keyword "antenatal visit K4" with vulnerable time 2018-2021. Review Methods: Literature review methods based on established criteria, then collected and made journal summaries include the name of the researcher, the year of publication of the journal, the title of the study, the method, and a summary of the results or findings. Summary of the research journal is entered into the table according to the format. Results: The search obtained 435 articles after filtering the year, namely 2018-2021, obtained 204 articles, then selected the category of journals, duplication, open access, and essay research has taken, namely mix methods study, cross sectional correlation analysis, and qualitative study. I got 48 articles. The final process is to conduct journal selection based on inclusion criteria obtained by nine journals that are eligible for review of the nine articles that meet the criteria obtained results. Namely, the role of health workers affects the scope of antenatal services K4. Conclusion: The role of health workers affects the increase in antenatal coverage of K4 so that it is expected that health workers/midwives further increase counseling for mothers in health centers and Posyandu activities, conduct door to door activities in each region, and provide a schedule of examinations to the mother so that the mother knows when to do a pregnancy examination, and improving the friendliness of health workers to mothers who conduct pregnancy examinations so that every complaint from the mother can be answered.